A UTILIZAÇÃO DE NOVAS TECNOLOGIAS NA ELABORAÇÃO DE PROJETOS DE HABITAÇÕES DE INTERESSE SOCIAL - Sousa Filho, José Alexandre; Alves, Karoliny Barbosa; Brandão, Clarissa de Faria; Jereissati, Geórgia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The construction industry is affected by the current economic crisis, so companies are looking for alternatives to lower costs and one way is to bet on using new technologies, such as design software, in which the project is digitally represented, and the customer may have more information and data about the building, thus diminishing the unforeseen in the process. Another technique is lean construction, where companies seek to reduce losses. This study combines design software and Lean, aiming to prepare the value stream mapping (VSM), a lean tool, in the modeling of an Architectural project, in order to identify and eliminate waste in the process, beyond its costs. In this quantitative research, a case study was used for an interest social house. Through the current VSM and identification wastes, it was suggested the future VSM, aiming elimination waste of the process, reduction of the cycle time, leveling of the activities. It was suggested a reduction of 19.10% in the Lead Time and 16.36% in the Processing Time. The study ratifies the idea that solutions based on the lean allied to software designs improve quality of the final project, as well as reduce the time, therefore the price of the projects.